A new European species of Drymeia Meigen (Diptera: Muscidae) near D. brumalis (Rondani), with observations of a unique prestomal teeth structure - Michelsen, Verner (Zootaxa, 2011)
A new species of Drymeia Meigen, D. pyrenaea sp. nov. is described and distinguished from the very similar D. brumalis (Rondani) based on material from northern Spain and Portugal. It is argued that records of D. brumalis and possibly even D. alpicola (Rondani) from outside Europe are probably based on misidentifications. A previously unnoticed, unique prestomal teeth structure is reported from several species of Drymeia. Preliminary observations show a remarkable diversity in prestomal teeth structure among species of Drymeia. This is documented by images of flat mounted labella.